Prevention of Hypertension Emergency Through Community Empowerment in the Working Area of Puskesmas Pacar Keling, Pucang Sewu, and Tambakrejo Surabaya - Jujuk Proboningsih (Frontiers in Community Service and Empowerment, 2023)
Hypertension is a chronic disease that has earned the title of the silent killer because its symptoms are often without complaint. Many people with hypertension are unaware of their disease for a long time, as the appearance or recognition of symptoms of the disease takes some time. Patients realize their disease after experiencing complications. The target is expected to have good knowledge and understanding of the care and prevention of hypertension patient emergencies, can apply in their daily lives as an effort to manage their disease in order to obtain optimal blood pressure, continue to carry out routine controls to the Puskesmas and take medicine regularly, consume appropriate food in the right amount and do regular and sufficient physical activity. Activities were carried out from June to August 2022, targeting 75 people and health cadres. The method used in the implementation of activities in the form of lectures and questions and answers about healthy living behavior to prevent emergencies in hypertensive patients, demonstrations of measuring blood pressure, BMI, determining salt requirements, regulating daily diet, and hypertension exercises. The media used are modules on healthy living behaviors to prevent emergencies and demonstrations of hypertension exercises. The results and outcomes of community service that have been carried out are almost all (86.7%) female participants, most (52.1%) are ≥61 years old, almost all (93.3%, 97.3%) are Muslim and Javanese, most (58.7%) in the family have no history of hypertension, most (64%) systole pressure ≥ 140 mmHg, most (56%) diastole pressure ≥ 90 mmHg and most (50.7%) cholesterol levels ≥ 200 mmHg. The results of this community service can be used as a motivation to increase community participation in making efforts to prevent and treat hypertension emergencies early in the Pucang Sewu, Pacar Keling, and Tambak Rejo Puskesmas areas, becoming a starting point for the realization of residents who are able to control blood pressure by regulating diet, obeying taking medication, and hypertension exercises and doing regular activities and materials to improve the performance of the Puskesmas while increasing the range of health services for the Puskesmas. INDEX TERMS Prevention, hypertension emergencies, community empowerment